نعمى " نمذوجا الشعر القصصي في كتاب خلجات ونبضات لإبراهيم سعيد أحمد الغنمبري : قصيدة " مجنون Arabic narrative poetry in Ibrahim Sa’id Ahmad Gambari’s Khalijat Wannabdat’s book: Majnun Nu’umah poetry as a paradigm (2024)
Despite the quantum commitments and immense contributions of Nigerian Arabic poets into Arabic literary genres, led to the production of their anthologies in different themes and styles. Arabic narrative poetry has not been favourably received the great attentions of Nigerian Arabic scholars like other genres. Therefore, Al-Khalijat Wanabdat of Ibrahim Sa’id Ahmad Gambari is to be examined by looking at the concept of Arabic Narrative Poetry and its rationale in Arabic literary heritage. Likewise, the emergence of Arabic Narrative Poetry in Nigerian Authorship and how it is specially explored in Ibrahim Sa 'id Ahmad Gambari’s poetry would be discussed.